In-Vitro Differentiation of Mature Dendritic Cells From Human Blood Monocytes - Gieseler, Robert (Hindawi Publishing Corporation, 1998)
Representing the most potent antigen-presenting cells, dendritic cells (DC) can now be generated from human blood monocytes. We recently presented a novel protocol employing GM-CSF, IL-4, and IFN-γ to differentiate monocyte-derived DC in vitro. Here, such cells are characterized in detail. Cells in culture exhibited both dendritic and veiled morphologies, the former being adherent and the latter suspended. Phenotypically, they were CD1a(-/dim), CD11a(+), CD11b(++), CD11c(+), CD14(dim/-), CD16(a-/dim), CD18(+), CD32(dim/-), CD33(+), CD40(+), CD45R0(+), CD50(+), CD54(+), CD64(-/dim), CD68(+), CD71(+), CD80(dim), CD86(+/++), MHC class I(++/+++) HLA-DR(++/+++) HLA-DP(+), and HLA-DQ(+). The DC stimulated a strong allogeneic T-cell response, and further evidence for their autologous antigen-specific stimulation is discussed. Although resembling a mature CD 11c(+)CD45R0(+) blood DC subset identified earlier, their differentiation in the presence of the Thl and Th2 cytokines IFN-γ and IL-4 indicates that these DC may conform to mature mucosal DC.